Legal Protection For Passanger In The Event Of An Accident On The Ship By Regulation Number 17 Of 2008 Concerning Shipping - Semuel Dumak Parerungan; Upik Widyaningsih; Femmy Asdiana (International Journal of Law and Legal Ethics, 2022)
On the basis of the foregoing, Law No. 17 of 2008 concerning Shipping which is a refinement of Law Number 21 Years 1992, so that the operation of shipping as a system can provide the greatest benefit to all the people, nation and country, cultivate and develop a maritime spirit, by prioritizing public interest, and environmental sustainability, coordination between the center and the regions, as well as state defense and security. The aim of this research is to describe policy issues regarding passanger protection on shipping accident.Based on the explanation that has been given, this study provides the following key conclusions: Legal protection for related ship passengers with the accident divided into two parts, namely the efforts made preventive and repressive measures. Preventive Effort is a preventive measure, it must be done in order to avoid accidents on the ship. Where preventive efforts are readiness is not only done in the readiness of the ship itself, but the readiness of the port is also involved taken into account considering that many factors can lead to accidents both internal factors as well as the external itself, as well as the distance travelled distant ship. This readiness is in the form of preparation documents and equipment on the ship so that it can running optimally. Repressive measures taken by following all directions from the crew and other competent authorities, as well as all of these actions by remaining calm and not panic, it was done with a purpose minimize further and more fatal losses such as loss of life during an accident.